2022
DOI: 10.1177/23328584221084722
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health Impacts of COVID-19 on PK–12 Students: A Systematic Review of Emerging Literature

Abstract: The mental health impact of the coronavirus disease 2019 (COVID-19) pandemic on PK–12 youth is likely an urgent and enduring concern, yet research on this topic is still emerging. To synthesize current knowledge, the researchers conducted a systematic review of empirical studies exploring the mental health impacts of COVID-19. Five themes emerged across 104 included studies: (a) the pandemic proved widely disruptive to PK–12 youth; (b) there was a clear connection between the mental health of caregivers (e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 303 publications
1
25
0
Order By: Relevance
“…Finally, not only is there evidence that care provided by SBHCs achieves high levels of satisfaction from students (Charette et al, 2019 ; O'Leary et al, 2014 ; Silberberg & Cantor, 2008 ; Zarate et al, 2020 ), but that it is also highly cost‐effective (Fisher et al, 2019 ) and offers large social benefits (Ran et al, 2016 ). Given this body of knowledge, SBHCs may be particularly helpful during the ongoing pandemic as well as during the long‐term recovery (Anderson et al, 2020 ; Hoffman & Miller, 2020 ; Naff et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, not only is there evidence that care provided by SBHCs achieves high levels of satisfaction from students (Charette et al, 2019 ; O'Leary et al, 2014 ; Silberberg & Cantor, 2008 ; Zarate et al, 2020 ), but that it is also highly cost‐effective (Fisher et al, 2019 ) and offers large social benefits (Ran et al, 2016 ). Given this body of knowledge, SBHCs may be particularly helpful during the ongoing pandemic as well as during the long‐term recovery (Anderson et al, 2020 ; Hoffman & Miller, 2020 ; Naff et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al (2021) found that parental social isolation and recent employment loss were positively associated with child maltreatment risk during the early stages of the pandemic among a US sample of parents. A systematic review has also highlighted that the mental health of caregivers was associated with children's mental health outcomes (Naff, Williams, Furman-Darby, & Yeung, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…provide such essential services as breakfasts and lunches, medical care, and behavioral health supports to students and families who depended on receiving them through school. The lack of other school-based experiences, such as physical activity, interpersonal connections, and social, emotional, and behavioral learning, did not cause the same immediate distress, but the potential ramifications of their absence are beginning to appear as anxiety and other mental and behavioral health challenges have increased among students (Hafstad, Augusti, 2021;Naff et al, 2022;Viner et al, 2022). COVID-19 has led to stress and feelings of grief and loss in youth and families who worry about the health of loved ones, job security and the economy, and who miss their established routines and friends.…”
mentioning
confidence: 99%
“…With students spending most of their day in schools and interacting with teachers and school staff, schools are at the forefront of the social, emotional, and behavioral consequences of the last two years on our children and youth. There are reports that behavior challenges have increased, social cues are not as understood, and the ability to share and interact with peers has decreased (Blad, 2022;Naff et al, 2022;Sun et al, 2022). There are also reports of increases in fighting, emotionally hurtful interactions, and absenteeism (Belsha, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation